PENGARUH COVID19 TERHADAP AKTIVITAS PERTUMBUHAN EKONOMI DI INDONESIA - Lenti Iswari; Muharir Muharir (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2021)
Activity restrictions due to the Covid-19 pandemic have affected national economic activity. Restrictions on community activities have an effect on business activities which in turn have an impact on the economy. The economic influence during the Covid period will only be covered in the crisis can be ended before it causes mass business bankruptcy. However, at this time there have been several business activities that have gone out of business and have cut off the work of thousands of workers. President Joko Widodo (Jokowi) declared the Corona virus pandemic (Covid-19) to be a heavy blow to the Indonesian economy. Not only that, the pandemic has also caused world economic growth to slow down.